Bias Gender Dalam Pemberian Gelar Bangsawan Terhadap Anak - Baiq Sabatari; Lalu Hendri Nuriskandar (Jurnal Syntax Transformation, 2022)
This study aims to find out the causes of gender bias in granting noble titles to children in Banyu Urip Village. When a noble woman marries a non-aristocratic man, the woman is considered to have violated adat and gets punished for what has been violated. This is inversely proportional to the treatment received by noble men who are not considered to have violated and do not get punished if noble men marry non-aristocratic women. Furthermore, in this study the author uses a type of qualitative research. The data collection procedure was carried out by means of interviews and observations, as well as taking from the supporting literature to serve as a reference. The data analysis technique was carried out by means of data reduction, data presentation, and drawing conclusions/verification. Based on the final results of this research activity, the authors suggest that when a noble woman marries a non-aristocratic man, her child will not get a nobility title, while a noble man marries a non-noble woman and their child still gets a nobility title. This is because: first, a man is the biological father of the child. Second, the ajirkrame of the nobility is higher than the ajirkrame of the common people. Third, because the nobility of women has been merged. Fourth, because it has been enforced or bought. This gender bias in the stratification of women of the Sasak nobility occurs because women are in a subordinated position, women tend to be marginalized, and the stereotype says that women are in a weak position while men are on the other hand in a superior and strong position..